Fabrication and Performances of Recessed Gate AlGaN/GaN MOSFETs with Si₃N₄/TiO₂ Stacked Dual Gate Dielectric - An, Hee-Dae; Bae, Jin-Hyuk; Lee, Sin-Hyung; Kang, In-Man; Min, So-Ra; Lee, Sang-Ho; Park, Jin; Kim, Geon-Uk; Yoon, Young-Jun; Seo, Jae-Hwa; Cho, Min-Su; Jang, Jaewon (Journal of semiconductor technology and science, 2022)
In this paper, a recessed gate AlGaN/GaN metal-oxide-semiconductor field-effect-transistor (M-OSFET) with Si3N4/TiO2 stacked dual gate dielectric was proposed and fabricated to improve the current drivability. Normally-off operation with a Vth of 1.81 V was obtained using a Cl2-based gate recess etching process. Dual gate dielectric technology was used to improve the current characteristics that can be degraded by damage resulting from gate recess etching. Compared to the single gate dielectric (Si3N4 = 30 nm)-based device, the ID,max and gm of the dual gate dielectric (Si3N4/TiO2 = 10/20 nm)-based device were improved by 292% and 195%, respectively. Moreover, the Ron and SS were improved by 62% and 68%, respectively. Breakdown voltage decreased by 1.4%, but there was minor difference. Therefore, the technique of depositing Si3N4 on GaN and then stacking high-k TiO2 can improve the current characteristics by increasing the capacitance through a simple process. As such, the recessed gate AlGaN/GaN MOSFETs with Si3N4/TiO2 stacked dual gate dielectric has the potential for high-efficiency power devices. KCI Citation Count: 1